Congenital Hypothyroidism - Hisworo Multialam; Robert M. Simandjuntak; Endang D. Hamid (Indonesian Pediatric Society Publishing House, 2018)
We report a case of congenital hypothyroidism seen at the Division of Endocrinology, Medical School, University of North Sumatera/Dr. Pirngadi Hospital. A 13-month ols Batak girl presented witih signs and symptoms of congenital hypothyroidism. On physical examination, umbilical and inguinal hernias were present. Treatment with L -Thyroxme using initial dose 45/µg/day for one month was initiated and after two months the signs and symptoms disappeared. Laboratory finding showed normal T4, but T3 was slightly low. Radiological examination was done to evaluate the bone age. The treatment was continued using the follow-up dose of L-Thyroxine 45µg. Although the treatment has resulted in good outcome,  evaluations for the child's growth and development should be continued.